Increased basal oxidation of peroxiredoxin 2 and limited peroxiredoxin recycling in glucose-6-phosphate dehydrogenase-deficient erythrocytes from newborn infants - Cheah, FC; Peskin, AV; Wong, FL; Ithnin, A; Othman, A; Winterbourn, CC (Federation Amer Soc Exp Biol, 2024)
Erythrocytes require glucose-6-phosphate dehydrogenase (G6PD) to generate NADPH and protect themselves against hemolytic anemia induced by oxidative stress. Peroxiredoxin 2 (Prx2) is a major antioxidant enzyme that requires NADPH to recycle its oxidized (disulfide-bonded) form. Our aims were to determine whether Prx2 is more highly oxidized in G6PD-deficient erythrocytes and whether these cells are able to recycle oxidized Prx2 after oxidant challenge. Blood was obtained from 61 Malaysian neonates with G6PD deficiency (average 33% normal activity) and 86 controls. Prx2 redox state was analyzed by Western blotting under nonreducing conditions. Prx2 in freshly isolated blood was predominantly reduced in both groups, but the median level of oxidation was significantly higher (8 vs 3%) and the range greater for the G6PD-deficient population. When treated with reagent H2O2, the G6PD-deficient erythrocytes were severely compromised in their ability to recycle oxidized Prx2, with only 27 or 4% reduction after 1 h treatment with 0.1 or 1 mM H2O2 respectively, compared with > 97% reduction in control erythrocytes. The accumulation of oxidized Prx2 in oxidatively stressed erythrocytes with common G6PD variants suggests that impaired antioxidant activity of Prx2 could contribute to the hemolysis and other complications associated with the condition.